A Critical Analysis of Language Variation In The Traditional Art Market Senggigi and Sade (Sociolinguistic Studies) - Wirata, I Wayan; Rahman, Arif (Jurnal Pendidik Indonesia (JPIn), 2021)
The researcher interested in language variations that occur in the traditional markets of Senggigi West Nusa Tenggara and Traditional House of Sade. Thus, this study analyzes the language variations in the process of buying and selling in the realm of Senggigi traditional markets and Traditional House of Sade. The author conducted research by taking the title "A Critical Analysis of Language Variation in the Senggigi Art Market and Traditional House of Sade (Sociolinguistic Studies)". Method used in this study is qualitative with data collecting technique with observation In this research, there was one type of data. The qualitative data consist of interview transcripts and observation sheets report in the form of field notes. These data were analyzed namely data display until final reporting. The findings of this research shows that there are several kinds of the language variation used by people in trading transaction at Senggigi art market, I.e., a) variation in term of speaker base on sociolect (dialek social) is concerning all personal problems of speaker such as age, sex, and social economy condition and b) Language variation in term of formality base on formal variety, Variety of Consultative Variety, casual variety, and Familiar Variety or Intimate Variety. There are factors influence of language variation base on situational factor. Situational factors include who speaks, to whom to speak, what language to use, where, when and what. and Language variation function mention related to sociolinguistic language functions namely instrumental functions, representational functions, interactional functions, and personal functions. There are The implications of the variety of languages used in communication in the traditional art markets of Senggigi and Sade are as follows: 1) Improve Social Interaction Relationships; 2) Increase Intelligence in Communicating; 3) Increase Income; and 4) Increasing Regional Cultural Identity.